1979
DOI: 10.1139/m79-113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antiserum agar method for the serogroup identification of Neisseria meningitidis

Abstract: The antiserum agar method (ASA), which is based on the formation of immunoprecipitates around bacterial growth on agar containing meningococcal hyperimmune horse serum, was evaluated for serogroup identification of Neisseria meningitidis. Four hundred meningococcal stains were serogrouped by ASA employing horse antisera to serogroups A, B, C, Y, W135, Z, and 29E and compared to serogroup identification by bacterial slide agglutination (BA) employing rabbit antisera. Overall, there was 95% agreement between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Serogroup determination was done by standard bacterial agglutination test (22) using rabbit antisera against all 13 serogroups (A, B, C, D, H, I, K, L, W135, X, Y, Z, and 29E) (2). Detection of serogroups A, B, C, W135, X, Y, Z. and 29E by PCR was accomplished using primers and PCR conditions described by Borrow and colleagues (in 1997 and 1998), Taha (in 2000), and Bennett et al (in 2004) (3)(4)(5)32).…”
Section: Methodsmentioning
confidence: 99%
“…Serogroup determination was done by standard bacterial agglutination test (22) using rabbit antisera against all 13 serogroups (A, B, C, D, H, I, K, L, W135, X, Y, Z, and 29E) (2). Detection of serogroups A, B, C, W135, X, Y, Z. and 29E by PCR was accomplished using primers and PCR conditions described by Borrow and colleagues (in 1997 and 1998), Taha (in 2000), and Bennett et al (in 2004) (3)(4)(5)32).…”
Section: Methodsmentioning
confidence: 99%
“…Rabbit antisera to the capsular polysaccharide antigens of serogroups A, B, C, W135, X, Y, Z, and 29E were produced according to the method described by Ashton et al (2). Albino rabbits were immunized by intravenous injections of a viable suspension of the bacteria adjusted to a cell density equivalent to a turbidity of a McFarland number 3 standard.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial agglutination test to determine the serogroup identity of meningococci was done as described by Ashton et al (2).…”
Section: Methodsmentioning
confidence: 99%
“…The capsular polysaccharide was isolated and partially purified as previously described (14) using an initial Cetavlon precipitation to obtain the crude polysaccharide. Purification of the K polysaccharide was achieved by its application to a column of DEAE-Sephadex A-25 (C1-form, Pharmacia Fine Chemicals) in 0.01 M Tris-HC1 buffer at pH 7.4 and the development of the column with a linear gradient of NaCl to 0.5 M. The plysaccharide was detected by Ouchterlony immunodiffusion using antisera to the K polysaccharide that were prepared by injecting whole group K organisms in rabbits as previously described (15). Using this assay it was shown that the K polysaccharide eluted as a single peak with approximately 0.3 M NaCI.…”
Section: Methodsmentioning
confidence: 99%